1994
DOI: 10.1007/bf01051049
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for cerebral glioma in adults: a case-control study in an Italian population

Abstract: A case-control study on risk factors for cerebral tumors was conducted on an adult Italian population by the four Neurosurgical Departments of the Veneto Region, i.e. Padua, Treviso, Verona and Vicenza. The study recruited 195 cases of histologically-confirmed cerebral glioma. One hospital control was selected for each case. Cases and controls were matched for age, sex, data of hospitalization and residence. Information on both cases and controls was obtained from a relative. Uninvolved interviewers administer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
42
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 31 publications
2
42
0
Order By: Relevance
“…One study demonstrated significantly more cases that were blood group A or AB (Selverstone and Cooper, 1961), while in another study, a significant excess of individuals with blood group A was observed in males but not in females (Garcia et al, 1963). However, our findings are consistent with several studies that showed no difference in the distribution of blood groups between cases and controls with glioma (Choi et al, 1970;Zampieri et al, 1994).…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…One study demonstrated significantly more cases that were blood group A or AB (Selverstone and Cooper, 1961), while in another study, a significant excess of individuals with blood group A was observed in males but not in females (Garcia et al, 1963). However, our findings are consistent with several studies that showed no difference in the distribution of blood groups between cases and controls with glioma (Choi et al, 1970;Zampieri et al, 1994).…”
Section: Discussionsupporting
confidence: 71%
“…While some evidence exists implicating certain work chemicals (Burch et al, 1987;Preston-Martin and Mack, 1991;Morrison et al, 1992), investigations of a wide range of genetic and environmental factors have been inconclusive (Burch et al, 1987;Wrensch and Barger, 1990;Schiffer, 1991;Ryan et al, 1992;Zampieri et al, 1994).…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Inskipp et al [12] suggested that severe head trauma slightly increases the overall risk of brain tumors. Similarly, Salvati et al [21] believe in an etiological association between severe head trauma and glioma development whereas others [22][23][24] consider that there is no clear correlation between cranial trauma and subsequent glioma formation. However, these studies included all types of head injuries (mild, moderate and severe) and could not rule out the possible effect of a severe cranial trauma.…”
Section: Discussionmentioning
confidence: 99%
“…Three studies were considered to be ineligible for inclusion in the analysis for the following reasons: (i) in one study, the definition of exposure to smoking was based on a high dose (C20 cigarettes/day) only [24]; (ii) another study [25] was based on the same study population as that of a later study [14], which provided a more comprehensive analysis of smoking and glioma; (iii) an additional study was excluded because the odds ratios for the smoking variables were not presented, but simply described as ''at unity,'' with no confidence intervals or p values [12].…”
Section: Methodsmentioning
confidence: 99%